Programs and Activities for Gifted Youth at Pillar University - Irina I. Ukraintseva; Galina M. Konovalova; Andrey V. Tambovtsev; Olga V. Bergen; Daria A. Pushkareva (Высшее образование в России)
An important task of pillar university within the framework of the implementation of the “third mission” is the work with gifted schoolchildren and youth of the region. The education programs and activities are aimed at involving them in scientific and innovation activities, identifying talents, early career guidance, attracting talented students to the region. For this purpose, Sochi State University has developed a number of projects of various target orientations, including with partners (Educational Center “Sirius”, ANO “Sea of Ideas”, etc.), which allows us to expand the geography of admission and raise the initial level of applicants’ training. This article presents the experience of SSU in working with talented schoolchildren and young people, including such projects as the organization of the All-Russian Multidisciplinary Engineering Olympiad “Zvezda”, Classes with talented schoolchildren in preparing them for participation in competitions, “Venture Accelerator”, “Improving teachers’ qualification to work in regional research and educational centers”, “Formation of a sociological portrait of applicants, students and graduates of educational programs of secondary vocational education providing training for the most popular, new and promising professions and specialties of secondary vocational education”.